2021
DOI: 10.3389/fpsyt.2021.654071
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Topographical Disorientation With Concurrent Face Recognition Deficit: A Case Report

Abstract: Developmental topographical disorientation (DTD) has been defined as a developmental deficit in human navigational skills in the absence of congenital or acquired brain damage. We report the case of Lost In Space Again (LISA), a 22-year-old woman with a normal development and no clinical history of neurological or psychiatric diseases, evaluated twice, with an interval of 5 years. The magnetic resonance imaging (MRI) examination did not reveal any morphological alteration, while diffusion tensor imaging (DTI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Differently from Burles and Iaria [ 12 ], we found that males are more affected than females by DTD with a ratio of 4:1. This finding is in line with the single cases described in literature, given that we identified more males [ 3 , 6 , 7 , 9 ] than females [ 1 , 8 , 23 ]. It is worth emphasizing that the two samples are not equivalent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Differently from Burles and Iaria [ 12 ], we found that males are more affected than females by DTD with a ratio of 4:1. This finding is in line with the single cases described in literature, given that we identified more males [ 3 , 6 , 7 , 9 ] than females [ 1 , 8 , 23 ]. It is worth emphasizing that the two samples are not equivalent.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, even the case described by Piccardi et al [ 9 ] that had both developmental landmark agnosia and developmental prosopagnosia, the treatment of developmental prosopagnosia had produced positive effects on developmental landmark agnosia by greatly reducing its symptoms. However, with respect to single case studies, just two cases showed the co-occurrence of a landmark agnosia and prosopagnosia [ 9 , 23 ]. This co-occurrence is also reported in acquired deficits [ 24 , 25 ] indicating a general difficulty in accessing similar stored representations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reliable, but slight self-reported impairments in some object, place, and face recognition in individuals with DTD ( Piccardi et al. 2019 ; Burles and Iaria 2020 ; Rusconi et al. 2021 ), these connectivity changes may be representative of weaker functional specialization within visual processing regions for special classes of objects, places in particular, in which individuals with DTD report difficulty processing relative to controls ( Burles and Iaria 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent case study of developmental topographic disorientation reported no morphological changes in MRI. However, DTI results suggested that etiology is associated with disrupted ber connections and decreased FA values, both of which occur in the prefrontal and prefrontal lobe-motor pathways [11].…”
Section: Introductionmentioning
confidence: 99%